SMART ASSISTANT FOR BLIND PEOPLE USING RASPBERRY PI 3 - A., Manonmani; M., Arivalagan; M., Lavanya; S., Sellakumar (International Journal of Psychosocial Rehabilitation, 2020)
An optical character recognition (OCR) system, which is a branch of computer vision and in turn a subclass of artificial intelligence. Optical character recognition is the translation of optically scanned bitmaps of printed or handwritten text into audio output by using a Raspberry Pi. OCRs developed for many world languages are already under efficient use. This method extracts moving object regions by a mixture-of-Gaussians-based background subtraction method. Text localization and recognition are conducted to acquire text information. To automatically localize the text regions from the object, a text localization and tesseract algorithm by learning gradient features of stroke orientations and distributions of edge pixels in an Ada boost model. Text characters in the localized text regions are then binaries and recognized by off-the-shelf optical character recognition software. The recognized text codes are output to blind users in speech. Performance of the proposed text localization algorithm. As the recognition process is completed, the character codes in the text file are processed using a Raspberry Pi device, which recognizes characters using the tesseract algorithm and Python programming. The audio output is listed.